Evaluasi Nutrisi Silase Kultivar Baru Tanaman Sorgum (Sorghum Bicolor) dengan Penambahan Legum Indigofera sp. pada Taraf Berbeda - Yayang Lilik Abdul Holik; Luki Abdullah; Panca Dewi Manu Hara Karti (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2019)
Sorghum is a source of fiber which is very potential to be cultivated and developed for forage production. Silage is a forage preservation method based on lactic acid fermentation under anaerobic conditions. Indigofera sp. is a tropical leguminous trees source with high protein content. Indigofera has an advantages in production and quality. The research was purposed to analyze the quality of sorghum varieties with the addition of Indigofera sp. different. Materials used in this study include Hybrid 20 sorghum plants, sorghum plants 12FS9006, sorghum plants 13FB7001, sorghum plants 12S49001, Indigofera sp. Plants with levels (0%, 10%, 15%, and 20%), EM4 and molasses. The equipments for making silage consisting of coper to chop up sorghum plants, scales, sprayers, shovels, sorghum compaction equipment, silos in the form of plastic buckets with plastic bags. The data was analyzed a multiple regression data normality test using Independent T-method. The results showed that silase sorghum 12FB7001 had higher water contenct, ash content and crude fat, whereas sorghum hybrid 20 had higher protein content and crude fiber. Sorghum 12FS9006 produced good quality silage (NH3, VFA, KCBK, and KCBO). It is concluded silage quality of the four sorghum cultivars than 0%, 10% and 20% levels. Keywords: sorghum cultivars, silage, Indigofera sp., quality, digestibility